Green process for chlorine-free benzaldehyde from the solvent-free oxidation of benzyl alcohol with molecular oxygen over a supported nano-size gold catalyst - Choudhary, Vasant R.; Dhar, A.; Jana, Prabhas; Jha, Rani; Uphade, B. S. (Green Chemistry, 2005)
Benzyl alcohol is oxidized selectively to benzaldehyde with high yield, with a little formation of benzylbenzoate, by molecular oxygen over a reusable nano-size gold catalyst supported on U3O8, MgO, Al2O3 or ZrO2 in the absence of any solvent.

Highly active and reusable catalyst from Fe-Mg-hydrotalcite anionic clay for friedel-crafts type benzylation reactions - Choudhary, Vasant R.; Jha, Rani; Choudhari, P. A. (Journal of Chemical Sciences, 2005)
Fe-Mg-hydrotalcite (Mg/Fe = 3) anionic clay with or without calcination (at 200-800 degrees C) has been used for the benzylation of toluene and other aromatic compounds by benzyl chloride. Hydrotalcite before and after its calcination was characterized for surface area, crystalline phases and basicity. Both the hydrotalcite, particularly after its use in the benzylation reaction, and the catalyst derived from it by its calcination at 200-800 degrees C show high catalytic activity for the benzylation of toluene and other aromatic compounds. The catalytically active species present in the catalyst in its most active form are the chlorides and oxides of iron on the catalyst surface.
Keywords: activation by calcinations; benzylation of aromatic compounds; benzylation of toluene; Fe-Mg-hydrotalcite

In-Mg-hydrotalcite anionic clay as catalyst or catalyst precursor for friedel-crafts type benzylation reactions - Choudhary, Vasant R.; Jha, Rani; Narkhede, V. S. (Journal of Molecular Catalysis A-Chemical, 2005)
In-Mg-hydrotalcite (Mg/In = 3) anionic clay with or without calcination (at 200-800 degrees C) or HCl pretreatment at different temperatures (26 and 80 degrees C) and periods (0.1 or 1.0 h) has been used for the benzylation of benzene and/or substituted benzenes by benzyl chloride. The hydrotalcite before and after its calcination or HCl pretreatment was characterized for its surface area, crystalline phases and basicity. The hydrotalcite particularly after its use in the benzylation reaction, and the catalyst derived from it by its calcination at 800 degrees C followed by HCl pretreatment (at 80 degrees C for 1.0 h), shows high catalytic activity even for the benzylation of benzene. The catalytically active species present in the catalyst in its most active form are the chlorides and oxides of indium on the catalyst surface. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: activation of In-Mg-hydrotalcite by calcination; activation of In-Mg-hydrotalcite by HCl pretreatment; benzylation of benzene; benzylation of substituted benzenes; In-Mg-hydrotalcite

GaClx- or GaAlClx-grafted Si-MCM-41: highly active and moisture insensitive/stable catalyst for the acylation and benzylation of benzene, naphthalene and substituted benzenes - Choudhary, Vasant R.; Jha, Rani (Applied Catalysis A-General, 2007)
GaClx- and GaAlClx-grafted Si-MCM-41 catalysts were prepared by reacting anhydrous GaCl3 and mixed anhydrous GaCl3 and AlCl3, respectively, with the terminal hydroxyl groups of Si-MCM-41 (pore size: 2.5 nm) in a dry non-aqueous reaction medium (CCl4) under reflux. The catalysts showed high activity for both the acylation and benzylation (with benzoyl chloride and benzyl chloride, respectively) of benzene, toluene, p-xylene, cumene, mesitylene, anisole and naphthalene. Both the catalysts are moisture insensitive or less moisture sensitive; the presence of moisture has a beneficial effect in the acylation over both the catalysts. The catalytically active sites of the GaClx-grafted Si-MCM-41 are (-O-)(2)GaCl (i.e. partially chlorided Ga anchored to Si through -O- linkage) species and the equivalent sites of the GaAlClx-grafted Si-MCM-41 are (-O-)(2)Ga(or Al)Cl and (-O-)(3)Ga(or Al) species. The high acylation/benzylation activities of both the catalysts even in the presence of moisture are attributed to their redox properties (Ga3+ -> Ga1+) rather than to their Lewis acid properties. After the grafting/chemical bonding, the grafted gallium chloride catalyst showed much higher acylation activity but lower benzylation activity than the physically deposited (on Si-MCM-41) or unsupported GaCl3. The GaAlClx-grafted Si-MCM-41 showed higher acylation activity than the GaClx-grafted Si-MCM-41, due to a synergetic effect of the Ga and Al species. However, the relative benzylation activity of the two catalysts showed strong dependence upon the presence or absence of electron donating group(s) and also upon the electron donating ability of the group(s) attached to the aromatic nucleus. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: acylation benzylation; GaAlClx-grafted Si-MCM-41; GaClx-grafted Si-MCM-41; moisture insensitive

Solvent-free selective oxidation of benzyl alcohol by molecular oxygen over uranium oxide supported nano-gold catalyst for the production of chlorine-free benzaldehyde - Choudhary, Vasant R.; Jha, Rani; Jana, Prabhas (Green Chemistry, 2007)
A detailed investigation on the production of chlorine-free benzaldehyde in the solvent-free oxidation of benzyl alcohol by O-2 over nano-gold supported on U3O8 has been carried out. Influence of different catalyst parameters (different methods of gold deposition on U3O8, gold loading and particle size, and catalyst calcination temperature) and reaction conditions (reaction period and temperature) on the process performance has been studied. The catalyst containing gold at higher concentration and with smaller gold particles showed the better process performance (higher benzyl alcohol conversion and benzaldehyde yield or selectivity). The benzyl alcohol conversion is largely increased but the selectivity for benzaldehyde is slightly decreased (while that of benzyl benzoate is increased) with increasing the reaction period or temperature. In the presence of solvent (viz. tolune, p-xylene, DMF or DMSO), the process performance was found to be inferior to that observed in the absence of any solvent. Substituted benzyl alcohols also can be oxidized by O-2 to corresponding aldehydes with high yield and/or selectivity, using the catalyst in the absence of any solvent.

Supported copper oxide as a highly active/selective catalyst for the epoxidation of styrene by TBHP to styrene oxide - Choudhary, Vasant R.; Jha, Rani; Chaudhari, Nitin K.; Jana, Prabhas (Catalysis Communications, 2007)
Liquid phase epoxidation of styrene by anhydrous and aqueous TBHP to styrene oxide has been studied under reflux, using different supported CuO (viz. Cuo/Si-MCM-41, CuO/Al2O3, CuO/Ga2O3 and CuO/In2O3) as easily separable and reusable heterogeneous catalysts. The CuO/Ga2O3 catalyst showed the best performance in the epoxidation by aqueous TBHP. The CuO supported on In2O3 or Si-MCM-41 also showed very good performance in the epoxidation but only by anhydrous TBHP. However, the CUO/SiO2 catalyst, however, showed very good performance in the epoxidation by both the anhydrous and aqueous TBHP. Influence of the reaction conditions (temperature, time and TBHP/styrene ratio) on the epoxidation by aqueous TBHP over the best catalyst (CuO/Ga2O3) has been investigated. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: CuO/Al2O3; CuO/Ga2O3; CuO/In2O3; Cuo/Si-MCM-41; CuO/SiO2; epoxidation; styrene; Styrene oxide; tertiary butyl hydroperoxide

GaAlCl(x)-grafted Mont.K-10 clay: highly active and stable solid catalyst for the friedel-crafts type benzylation and acylation reactions - Choudhary, Vasant R.; Jha, Rani (Catalysis Communications, 2008)
A liquid phase reaction of anhydrous GaCl(3) and AlCl(3) with the surface hydroxyl groups (with HCl evolution) of Mont. K-10 clay in dry CCL(4) under reflux resulted in a novel GaAlCl(x),-grafted Mont.K-10 catalyst [with Cl/(Ga + Al) = 1]. The catalyst showed high activity and stability in the Freidel-Crafts type benzylation and benzoylation (by benzyl chloride and benzoyl chloride, respectively) of benzene, naphthalene and substituted benzenes, even in the presence of moisture. It also showed good activity for the benzoylation of nitrobenzene (i.e. even in the presence of strong electron withdrawing group, like nitro group, attached to the benzene ring). The catalytically active surface species in the catalyst are -(O)(2)-Ga(or Al)Cl. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: benzoylation of aromatics; benzylation of aromatics; GaAlCl(x)-grafted Mont.K-10

Selective epoxidation of styrene to styrene oxide by TBHP using simple transition metal oxides (NiO, CoO or MoO3) as highly active environmentally-friendly catalyst - Choudhary, Vasant R.; Jha, Rani; Jana, Prabhas (Catalysis Communications, 2008)
Simple transition metal oxides, such as NiO, CoO or MoO3, etc. show high catalytic activity for the selective epoxidation of styrene to styrene oxide by TBHP. The order of choice for different transition metal oxides for epoxidation is NiO > CoO > MoO3 > Cr2O3 > Fe2O3 > ZnO >= U3O8 >> TiO2 >> MnO2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: CoO; epoxidation; MoO3; NiO; styrene; Styrene oxide; TBHP

Acylation of nitrobenzene and substituted nitrobenzenes by benzoyl chloride using GaClx- and GaAlClx-grafted meporous Si-MCM-41 catalysts - Choudhary, Vasant R.; Jha, Rani (Microporous and Mesoporous Materials, 2009)
A acylation of nitrobenzene and substituted nitrobenzene by benzoyl chloride can be accomplished with good yield in a short reaction period (<= 3 h), even in the presence of moisture, using GaClx- and GaAlClx-grafted mesoporous silica (Si-MCM-41) catalyst. The catalyst is reusable/environmentally friendly. The presence of moisture in the catalyst has beneficial effect on the acylation reaction. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Acylation; Benzoyl chloride; GaAlClx-grafted Si-MCM-41; GaClx-grafted Si-MCM-41; nitrobenzene